STOCK INVESTMENT BEHAVIOR: HEURISTICS AND INVESTMENT ETHICS AS AN INTERVENING VARIABLE FOR INVESTORS IN MAKASSAR (International Conference on Social and Islamic Studies, 2022)
Investor behavior plays an important role in making investment decisions in the capital market because an appropriate investment decision is not only based on fundamental factors as a rational aspect, but is also influenced by psychological factors, namely investor behavior which is an irrational aspect in stock trading and expectations of returns. received. This study aims to examine the influence of heuristics on investment behavior by using investment ethics as an intervening variable. The research method of this study is quantitative research. This study uses an associative approach. The associative approach is research that aims to determine the relationship between two or more variables. The population of this study are investors who invest in shares in the Indonesia Stock Exchange in Makassar City who are still actively investing. The sample criteria of thisstudy are investors who invest in shares in the Indonesia Stock Exchange in the city of Makassar. In addition, the investment criteria is to have a minimum time of 1-2 years. The results of the study show that the heuristic variable is a factor that also influences one's investment behaviour. This reveals that the higher the heuristic attitude or behaviour of an investor will also affect investment behaviour in making investment decisions. Heuristic variables or moral considerations have a positive influence on investment ethics. The investment ethics variable has a positive effect on investment behaviour. This happens because investors tend to always take moral considerations by observing the consequences that will occur both to the individual himself and also to his social environment in determining investment choices and attitudes. The heuristic variable has a positive effect on investment behaviour through investment ethics.